A novel MAC protocol for ad hoc networks. (12th December 2013) - Sabut, Priyadarshini; Ray, Niranjan Kumar; Turuk, Ashok Kumar
Efficiency of ad hoc networks depends on the performance and reliability of medium access control (MAC) protocol used to access the shared medium. Presence of hidden and exposed nodes in ad hoc networks degrade the performance of MAC protocol. IEEE 802.11 DCF was designed to overcome the above problems associated with ad hoc networks. However, the throughput and channel utilisation in IEEE 802.11 DCF is lower due to the inability of hidden and exposed nodes to either transmit or receive during the period of on–going transmission in its vicinity. In this paper we proposed a MAC protocol that not only overcomes the problem of hidden and exposed nodes but also allows the hidden nodes to transmit and expose nodes to receive without interfering with the ongoing transmission in their vicinity. We performed an extensive simulation using ns–2 simulator and compared our proposed MAC protocol with 802.11 DCF. The metrics considered for comparison are throughput, packet delivery ratio and control overhead. It is observed that the proposed MAC outperforms 802.11 DCF in terms of throughput and packet delivery ratio with a marginal increase in the control overhead.